S2 Heart Sound Detects Aortic Valve Calcification Independent of Hemodynamic Changes in Mice - Dargam, Valentina; Ng, Hooi Hooi; Nasim, Sana; Chaparro, Daniel; Irion, Camila Iansen; Seshadri, Suhas Rathna; Barreto, Armando; Danziger, Zachary C.; Shehadeh, Lina A.; Hutcheson, Joshua D. (Frontiers in Cardiovascular Medicine, 2022)
Background: Calcific aortic valve disease (CAVD) is often undiagnosed in asymptomatic patients, especially in underserved populations. Although artificial intelligence has improved murmur detection in auscultation exams, murmur manifestation depends on hemodynamic factors that can be independent of aortic valve (AoV) calcium load and function. The aim of this study was to determine if the presence of AoV calcification directly influences the S2 heart sound. Methods: Adult C57BL/6J mice were assigned to the following 12-week-long diets: 1) Control group (n = 11) fed a normal chow, 2) Adenine group (n = 4) fed an adenine-supplemented diet to induce chronic kidney disease (CKD), and 3) Adenine+HP (n = 9) group fed the CKD diet for 6 weeks, then supplemented with high phosphate (HP) for another 6 weeks to induce AoV calcification. Phonocardiograms, echocardiogram-based valvular function, and AoV calcification were assessed at endpoint. Results: Mice on the Adenine+HP diet had detectable AoV calcification (9.28 ± 0.74% by volume). After segmentation and dimensionality reduction, S2 sounds were labeled based on the presence of disease: Healthy, CKD, or CKD+CAVD. The dataset (2,516 S2 sounds) was split subject-wise, and an ensemble learning-based algorithm was developed to classify S2 sound features. For external validation, the areas under the receiver operating characteristic curve of the algorithm to classify mice were 0.9940 for Healthy, 0.9717 for CKD, and 0.9593 for CKD+CAVD. The algorithm had a low misclassification performance of testing set S2 sounds (1.27% false positive, 1.99% false negative). Conclusion: Our ensemble learning-based algorithm demonstrated the feasibility of using the S2 sound to detect the presence of AoV calcification. The S2 sound can be used as a marker to identify AoV calcification independent of hemodynamic changes observed in echocardiography.